2006
DOI: 10.1523/jneurosci.5398-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

BDNF Is Expressed in Skeletal Muscle Satellite Cells and Inhibits Myogenic Differentiation

Abstract: In skeletal muscle, brain-derived neurotrophic factor (BDNF) has long been thought to serve as a retrograde trophic factor for innervating motor neurons throughout their lifespan. However, its localization in mature muscle fibers has remained elusive. Given the postulated roles of BDNF in skeletal muscle, we performed a series of complementary experiments aimed at defining the localization of BDNF and its transcripts in adult muscle. By reverse transcription-PCR, in situ hybridization, and immunofluorescence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
165
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(180 citation statements)
references
References 57 publications
12
165
1
2
Order By: Relevance
“…Brain-derived neurotrophic factor (BDNF) belongs to the family of neurotrophins and is primarily produced in neurons and glia cells and to a lesser extent in endothelial cells (Leventhal et al, 1999), leucocytes (Kerschensteiner et al, 1999), and satellite cells in skeletal muscles (Mousavi and Jasmin, 2006). Brain-derived neurotrophic factor is important for growth of the central nervous system during fetal development, whereas in adults, BDNF is primarily involved in synaptic plasticity, neurogenesis, and neuronal survival (for review, see Waterhouse and Xu, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Brain-derived neurotrophic factor (BDNF) belongs to the family of neurotrophins and is primarily produced in neurons and glia cells and to a lesser extent in endothelial cells (Leventhal et al, 1999), leucocytes (Kerschensteiner et al, 1999), and satellite cells in skeletal muscles (Mousavi and Jasmin, 2006). Brain-derived neurotrophic factor is important for growth of the central nervous system during fetal development, whereas in adults, BDNF is primarily involved in synaptic plasticity, neurogenesis, and neuronal survival (for review, see Waterhouse and Xu, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the BDNF and TrkB receptors are also expressed in many non-neuronal tissues including muscle, thymus, vascular smooth muscle cells, lung and spleen 5,10,14,16,18,19,36 . However, in a number of different studies it has been found that BDNF receptors are not expressed in peripheral tissues.…”
Section: Discussionmentioning
confidence: 99%
“…BDNF expression was primarily detected in the hippocampus, cortex, and basal forebrain, areas where the brain performs learning, memory, and high-level thinking tasks 13 . Later, it was found that BDNF was presented not only in the brain but also in peripheral tissues such as skeletal muscle, adipose tissue, kidneys, liver and prostate 5,10,11,[14][15][16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, these cells may play a role by producing various neurotrophic factors (or their receptors), which may also be regulated by androgens. For example, skeletal muscle satellite cells produce brain derived neurotrophic factor (BDNF; Mousavi and Jasmin, 2006), and levels of both BDNF and its receptor TrkB are controlled by androgens in at least some motoneurons (Osborne et al, 2007;Ottem et al, 2007). It is thought that BDNF produced by the muscle acts as a retrogradely transported trophic factor to support motoneurons throughout their lifespan.…”
Section: Cultured Motoneuron-like Cellsmentioning
confidence: 99%